The Relationship Between Worker’s Knowledge and Compliance in Implementing the Occupational Health and Safety Program at PT. Moratelindo - Muhammad Syahrir; Asmiana Saputri Ilyas; A. Jusriadi; Chitra Dewi; Asrianto Saputra Ilyas (Media Informasi, 2026)
The rapid development of industry in the era of globalization has had a significant impact on occupational health and safety (OHS), including in Indonesia. The implementation of OHS programs is essential to prevent occupational accidents and work-related diseases, which continue to increase each year. This study aims to determine the relationship between workers’ knowledge and compliance in implementing the OHS program at PT Moratelindo Regional Makassar. This research employed an analytical survey design with a cross-sectional approach. The population consisted of all 37 workers at PT Moratelindo, with 32 respondents selected as samples using a total sampling technique. The results showed that most respondents had good knowledge of OHS (90.6%), and their level of compliance with implementing OHS programs was also high (96.9%). The chi-square statistical test revealed a significant relationship between workers’ knowledge and compliance with OHS implementation, with a p-value of 0.002 (< α = 0.05). It can be concluded that workers’ knowledge is significantly associated with their compliance in implementing OHS programs.